2017
DOI: 10.1007/s00417-017-3706-x
|View full text |Cite
|
Sign up to set email alerts
|

Is ellipsoid zone integrity essential for visual recovery in myopic neovascularization after anti-VEGF therapy?

Abstract: Twenty-two eyes (male, six; female, 16; mean age, 65 ± 14 years) were considered. Mean follow-up was 21.5 ± 14 months. Best-corrected visual acuity (BCVA) improved from 0.38 ± 0.26 to 0.16 ± 0.20 logMAR (p < 0.001). The ellipsoid zone and the external limiting membrane (ELM) were disrupted in 21 (95.5%) and 15 (68.2%) eyes at baseline, and in 16 (72.7%) and nine (40.9%) eyes after therapy respectively. The ellipsoid zone and ELM were typically intact at lesion margins in 13 (59.1%) and 19 eyes (86.5%) respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
4
1
Order By: Relevance
“…At the last visit, eyes with a continuous ellipsoid zone in the central fovea usually had better visual outcomes. This result is compatible with the findings of previous reports [ 15 , 16 , 24 , 25 ]. For eyes with a discontinuous ellipsoid zone, the SH may be thick and reach beyond the ellipsoid zone; thus, severe damage to the retinal structure may limit visual recovery after hemorrhage absorption [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…At the last visit, eyes with a continuous ellipsoid zone in the central fovea usually had better visual outcomes. This result is compatible with the findings of previous reports [ 15 , 16 , 24 , 25 ]. For eyes with a discontinuous ellipsoid zone, the SH may be thick and reach beyond the ellipsoid zone; thus, severe damage to the retinal structure may limit visual recovery after hemorrhage absorption [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…This was consistent with previous studies finding a BCVA correlation in EZ structural integrity ( 18 , 20 23 ). However, it is not consistent with Milani's view ( 24 ). He found that even in absence of EZ at baseline and final follow-up, it was observed to be increased BCVA.…”
Section: Discussioncontrasting
confidence: 84%
“…The integrity of the ellipsoid zone at baseline was also one of the factors predicting better final visual acuity after anti-vascular endothe-lial growth factor treatment in patients with myopic neovascularization. 9 These studies significantly improved our understanding of pathogenic mechanisms leading to vision loss in pathological myopia. Compared to qualitative observations, quantitative analysis would provide much more detailed information regarding small and seemingly minor changes, enabling early detection of photoreceptor degeneration.…”
mentioning
confidence: 99%